Tuibian-zhong-de-gugong = Taiwan's National Palace Museum in transition (Guanghua Zhuanbo Shiye Zonggongsi, 2003)
"Take a peek at the ongoing changes at the museum, such as privatization and active efforts to bring the cultural relics out of the secluded vaults of the palace to the people." -- Container